ANALISA PRINSIP KERJA FLOW SENSOR DALAM MENGETAHUI VOLUME TIDAL MESIN ANASTESI VENTILATOR - Kharisda Novtri Gratia Gulo; Siti Rahmah (JURNAL MUTIARA ELEKTROMEDIK, 2021)
Flow sensors have an important role in ventilator anesthesia machines, where flow sensors function to monitor air flow and pressure to obtain the amount of air volume and pressure delivered to the patient. If the volume of air entering the patient does not match the capacity of the patient's lungs, it can endanger the patient. So that a flow sensor is needed in order to know the accuracy of the volume that will be given to the patient.